The basic physics of the binary black hole merger GW150914. Issue 1 (4th October 2016) - ,; Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; et al.
Abstract : Advanced LIGO made the first gravitational‐wave detection on September 14, 2015. The GW150914 signal was strong enough to be apparent in the cleaned detector strain data. Those features of the signal visible in these data are analyzed, using only such concepts from Newton and general relativity as are accessible to anyone with a general physics background. This simple analysis presented here is consistent with the full published analyses, in showing that the signal was produced by the inspiral and merger of two black holes, and in estimating the distance from the Earth and the energy radiated in gravitational waves. Abstract : The first direct gravitational‐wave detection was made by the Advanced Laser Interferometer Gravitational Wave Observatory on September 14, 2015. The GW150914 signal was strong enough to be apparent, without using any waveform model, in the filtered detector strain data. Here, features of the signal visible in the data are analyzed using concepts from Newtonian physics and general relativity, accessible to anyone with a general physics background. The simple analysis presented here is consistent with the fully general‐relativistic analyses published elsewhere, in showing that the signal was produced by the inspiral and subsequent merger of two black holes. The black holes were each of approximately 35 M ⊙, still orbited each other as close as ∼350 km apart and subsequently merged to form a single black hole. Similar reasoning, directly from the data, is used to roughly estimate how far these black holes were from the Earth, and the energy that they radiated in gravitational waves.